Update on the current situation with respect to COVID-19 in UK. - Khan, Aamir (International Journal of Endorsing Health Science Research, 2021)
Currently, UK is experiencing a second wave of the Covid-19 virus. A new strain of the Covid-19 coronavirus has emerged in the UK, which is spreading more quickly than previous strains. The relative hazard of death within 28 days of a test in infected people compared to people with the original variant was 1.35 (95% confidence interval 1.08 to 1.68). That suggests it is more contagious. So, it's particularly important to be strict about social distancing, wearing a face mask in enclosed spaces, and frequently washing your hands. There is no evidence to suggest whether this strain is more deadly than before. Initial findings from a study conducted by Imperial College London and Ipsos MORI show infections increased by 50% from early December, with 1 in 63 people infected. The interim findings from the eighth report of Real-time Assessment of Community Transmission (REACT), one of the country's largest studies into COVID-19 infections in England, suggest that infections in England have plateaued at the highest level with suggestions of a potential uptick. The report does not yet reflect the impact of national lockdown.